Resilience of Sweet Chestnut and Truffle Holm-Oak Rural Forests in Languedoc-Roussillon, France: Roles of Social-Ecological Legacies, Domestication, and Innovations - Aumeeruddy-Thomas, Yildiz; Therville, Clara; Lemarchand, Cedric; Lauriac, Alban; Richard, Franck (Ecology and Society)
The Cvennes sweet chestnut (Castanea sativa Mill.) forest-orchards and the holm-oak (Quercus ilex L.) black truffle (Tuber melanosporum Vittad.) associations of the garrigue in Languedoc-Roussillon have suffered a century of decline because of great reductions of rural populations and lack of understanding of the ecological and social dimensions of these rural forests by sectorial public agencies. Levels of tree and forest domestication alternated during historical periods in parallel with statuses of disorganization and reorganization of local social groups. Social-ecological legacies intrinsically linked to trees, forests, and landscape domestication, as well as knowledge, social, and technical practices have been mobilized and provided a basis for knowledge innovations, new domestications, uses, and new institutional networks related to changes in social set-ups. Collective actions emerging from local needs to revive territories in a modern context, cross-scale and reciprocal exchanges of rural and scientific knowledge, as well as institutional changes are interrelated variables that have enabled innovations and have increased resilience of these rural forests. This paper opens new avenues for future research on the interplay between the effects of social-ecological legacies and innovations on the resilience of social-ecological systems.
Keywords: Cévennes; chestnut; domestication; Garrigue; holm-oak black truffle association; innovations; resilience; rural forests; social-ecological legacies

La gestion des taillis de chênes vert et pubescent dans les garrigues du Gard - Curt, Thomas (Ingénieries EAT, 1996)
Medium term management of ageing Holm Oak (Quercus ilex L.) and Downy Oak (Quercus pubescens Willd.) coppices in the Gard requires a thorough understanding of the natural environments and yields of the plantations. This paper puts forward a method for analysing the environment and plantation in order to assess the yield of the oak coppices. 118 small stands were studied in different types of coppices. In general, two environmental parameters determined the dominant height of the stand: geopedological conditions (rock, parent material and soil) and topoclimate which depends on the position of the plantation (orientation and topography). The growth height is affected by the structure and composi- tion of the plantation, together with the forestry and plant growth characteristics. Multivariate ana- lyses enabled 9 types and sub-types of sites to be distinguished with particular environmental con- ditions (soil and topoclimate). The type of site is closely correlated to the variation in the dominant height of the plantations. Growth classes are proposed for the Holm Oak (3 classes) and the Downy Oak (4 classes). These results should assist plantation management selection: the best coppices should possibly be allowed to develop as standards, plantations of average fertility should be treated as simple coppices, coppices with low growth rate should be allowed to grow on. 83
Keywords: Chêne pubescent; chêne vert; conditions geopedologiques (voyant); croissance en hauteur; Gard; Garrigue; peuplements; taillis

La gestion des taillis de chênes vert et pubescent dans les garrigues du Gard - Curt, Thomas (Ingénieries EAT, 1996)
Medium term management of ageing Holm Oak (Quercus ilex L.) and Downy Oak (Quercus pubescens Willd.) coppices in the Gard requires a thorough understanding of the natural environments and yields of the plantations. This paper puts forward a method for analysing the environment and plantation in order to assess the yield of the oak coppices. 118 small stands were studied in different types of coppices. In general, two environmental parameters determined the dominant height of the stand: geopedological conditions (rock, parent material and soil) and topoclimate which depends on the position of the plantation (orientation and topography). The growth height is affected by the structure and composi- tion of the plantation, together with the forestry and plant growth characteristics. Multivariate ana- lyses enabled 9 types and sub-types of sites to be distinguished with particular environmental con- ditions (soil and topoclimate). The type of site is closely correlated to the variation in the dominant height of the plantations. Growth classes are proposed for the Holm Oak (3 classes) and the Downy Oak (4 classes). These results should assist plantation management selection: the best coppices should possibly be allowed to develop as standards, plantations of average fertility should be treated as simple coppices, coppices with low growth rate should be allowed to grow on. 83
Keywords: Chêne pubescent; chêne vert; conditions geopedologiques (voyant); croissance en hauteur; Gard; Garrigue; peuplements; taillis